Santri Perception to Islamic Bank: Are there no Differences with Conventional Banks? - M. Fuad Hadziq; Yosi Mardoni; Moh. Khoirul Anam (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2021)
Several studies show no difference in practice and academics in general between Islamic banks and conventional banks. However, they are both very different. This research analysed the perceptions of santri/students of Islamic boarding schools regarding no differences between Islamic banks and conventional banks. This research was quantitative with an in-depth descriptive analysis. The research sample used a blend of purposive and judgment techniques applied to santri from several large Islamic boarding schools in Banyuwangi. The analytical method used a two-way causative relationship using multiple regression. The research used a structured questionnaire with a Likert scale and in-depth interviews with santri. Santri's view of Islamic banks differed from that of regular banks. Santri strongly believes in Islamic banking, while the majority is not traditional but represents Islamic ideals. Islamic bank workers, nevertheless, have shown Islam's greater identity than standard banks and imply that no disparities in Islamic banks are shown to be stigmatic.